Nadīra nāma Nirupamā - Baṛuẏā, Suparṇā Lāhiṛī (Setu Prakāśanī, 2017)
On the life and works of Nirupamā Baragohāñi, born 1932, eminent 20th century Assamese author
Keywords: Baragohāñi; Nirupamā 1932-; Authors; Assamese